The Role of In-Store Consumer Movements in Purchase Decision - Selim Çam; Murat Fatih Tuna (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Customer contact centres are one of the types of businesses that support digital operations, where goods and services are offered as a bundle of products. Through these centres, consumers can both access sub-services related to telecommunication services and purchase the technologies that will enable this access. The fact that the telecommunications sector has become a locomotive sector in many countries worldwide makes it necessary to understand customers' behaviour. At this point, it is also essential to investigate how they behave in contact centres, which are part of the holistic channel. This study examines the behaviour of store customers who visit contact centres using non-computational methods. The study also compares the observed behaviours according to demographic data and tries to understand the dynamics of the purchase decision process. In this way, the effects of shoppers' profile characteristics, in-store movements and store structure on the termination status and duration of shopping were revealed. While differences were detected according to gender, no significant differences were found according to age in the findings. Similarly, the importance of consumers' in-store movements for sales was presented. It is thought that the results obtained in the research will contribute to both customer contact centres and future research, especially the local authorities of the company where the store data is received.